HUBUNGAN ANTARA MINAT BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMA - Taa, Angela Anastasia; Liu, An Nisaa Al Mumin; Kaleka, Melkyanus (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2021)
This study aims to determine the relationship between learning interest and learning motivation on physics learning outcomes. The type of research used is correlational research with a quantitative approach. The population in this study were students of class X science at SMA Negeri 1 Wewewa Selatan in the 2019/2020 academic year. In this study, the sample was taken using a random sampling technique taken as many as 35 students. Data collection techniques were carried out through questionnaires and documentation. The data were analyzed using the Pearson product moment correlation test. The results show that there is a significant relationship between interest in learning and learning outcomes in physics. The results of the analysis obtained a significance value of 0.000 <0.05. Learning motivation and physics learning outcomes also show that there is a significant relationship. The results of the analysis obtained a significance value of 0.001 <0.05.